Implementation of Job Safety Analysis and HIRADC as Occupational Risk Control Strategies in the Preventive Maintenance Process at PT XYZ - Annisa Safitri Mawaddah; Setiawan Setiawan; Cipto Purwanto (Journal La Multiapp, 2026)
This research focuses on potential hazards and the risk of accidents that may occur during preventive maintenance, which requires awell planned approach. The objective of this study is to identify hazards, analyze the extent of the risks, and evaluate methods that canbe used to control those risks. Data collection was conducte dusing the JSA (Job Safety Analysis) method to identify hazards at each stage of the work and the HIRADC (Hazard Identification, Risk Assessment, and Determining Control) to assess risk levels and select appropriate control measures. The findings of this study revealthe presence of various potential hazards, such as mechanical, electrical, and human factors, with varying threat levels ranging from low to high Risk management includes administrative controls, the use of personal protective equipment, and inspections of the tools used. It is hoped that the application of the JSA and HIRADC methods can effectively assist in the identification and control of risks, although their implementation still requires improvement particularly regarding monitoring of worker compliance. It is recommended to enhance training on workplace safety and conduct periodic evaluations of risk control measures.